Examining the joint impact of relationship norms and service failure severity on consumer responses. Issue 1 (3rd March 2020) - Li, Zongchao; Tao, Weiting; Wu, Linwan
ABSTRACT: This study investigates consumers' attitudinal and behavioral outcomes after service failure encounters with companies with which they have previously established good relationships. It indicates that conformity with or violation of relationship norms guides consumers' decision making, and that their subsequent attitudinal and behavioral outcomes further depend on the severity of the service failure. Through a 2 (relationship norm types: exchange vs. communal) × 2 (service failure severity: minor vs. major) between-subjects experiment, the study shows that when the prior relationship norms are exchange-based, consumers demonstrate similar attitudes toward the minor and major failures. However, when these relationship norms are communally-based, consumers respond relatively positively in the minor failure situation, but they display more negative attitudes in the major failure situation. This study contributes to public relations literature regarding the role of company-consumer relationships in service failure situations.